The Role of Educational Factors in the Success of Corporate E-Learning: A Case Study - Nam, Selçuk; Tutar, Hasan (My University, 2023)
The main purpose of this study is to determine the role of critical success factors in corporate e-learning. The research was designed according to a holistic single case study, one of the qualitative research designs. According to the critical situation sampling, the research sample was determined, and the data were collected through semi-structured interviews with eight senior bank managers. The data were analyzed according to content analysis using the MAXQDA qualitative analysis package program. Analysis results show seven critical success factors for corporate e-learning: staying in the environment and continuity, content quality, compliance with learning goals, accessibility, content attractiveness, interaction, and corporate communication support. According to the analysis findings, staying in the environment and continuity are the most critical success factors in e-learning. This study offers an andrological framework at the institutional level instead of research that focuses on students generally and provides a pedagogical framework for evaluating e-learning success. The research results are essential in revealing the necessity of a macro perspective in evaluating the success of the e-learning ecosystem consisting of individuals, the environment, institutions, education, and technology. This research is also original and essential in contributing to the employees seeing the factors that prevent the benefit they expect from e-learning
Keywords: Corporate e-Learning; Adult Learning; E-Learning Success; Educational Factors